Perspektif Ayat-Ayat Al-Qur’an Tentang Psikologi Pendidikan - Hidayatullah, Syarif (Lembaga Yasin AlSys, 2023)
Psychology is a special science that focuses its discussion on the psychology that exists in humans. The goal of educational psychology is how to apply psychology to a process that brings about a better change in one's behavior. In this paper, we will describe how educational psychology relates directly to the verses in the Qur'an, as we all know that the meaning of education is the study of growth, learning, and personal maturity, how to apply the principles -scientific principles of humanitarian response. All behavior that exists in humans is a process of education, which can provide lessons, especially for individuals. fostering critical thinking skills through carrying out learning tasks, cultivating habits and participating actively on a regular basis to utilize and fill free time with learning activities. Islamic education as a means of business how an individual can develop and grow in a guided personality according to Islamic teachings. then in educational psychology related to the verses of the Qur'an there are 4 that must be considered, namely ar-ruh, an-nafs, al-qolb, al-aql.